Getting the message straight: effects of a brief hepatitis prevention intervention among injection drug users - Bluthenthal Ricky N; Singer Merrill; Green Traci C; Grau Lauretta E; Marshall Patricia A; Heimer Robert (BMC, 2009)
Abstract To redress gaps in injection drug users' (IDUs) knowledge about hepatitis risk and prevention, we developed a brief intervention to be delivered to IDUs at syringe exchange programs (SEPs) in three US cities. Following a month-long campaign in which intervention packets containing novel injection hygiene supplies and written materials were distributed to every client at each visit, intervention effectiveness was evaluated by comparing exposed and unexposed participants' self-reported injection practices. Over one-quarter of the exposed group began using the novel hygiene supplies which included an absorbent pad ("Safety Square") to stanch blood flow post-injection. Compared to those unexposed to the intervention, a smaller but still substantial number of exposed participants continued to inappropriately use alcohol pads post-injection despite exposure to written messages to the contrary (22.8% vs. 30.0%). It should also be noted that for those exposed to the intervention, 8% may have misused Safety Squares as part of pre-injection preparation of their injection site; attention should be paid to providing explicit and accurate instruction on the use of any health promotion materials being distributed. While this study indicates that passive introduction of risk reduction materials in injection drug users through syringe exchange programs can be an economical and relatively simple method of changing behaviors, discussions with SEP clients regarding explicit instructions about injection hygiene and appropriate use of novel risk reduction materials is also needed in order to optimize the potential for adoption of health promotion behaviors. The study results suggest that SEP staff should provide their clients with brief, frequent verbal reminders about the appropriate use when distributing risk reduction materials. Issues related to format and language of written materials are discussed.